Semanggi Surabaya Sebagai Sumber Belajar Berbasis Kearifan Lokal Pada Pembelajaran Ilmu Pengetahuan Alam dan Sosial di SDN Kandangan II/620 Surabaya - Kurniawan, Hima; Widodo, Wahono; Gunansyah, Ganes (Jurnal Ilmu Sosial dan Budaya Indonesia, 2025)
This study aims to explore the use of Semanggi Surabaya as a learning resource based on local wisdom in learning Natural and Social Sciences (IPAS) in grade IV of SDN Kandangan II/620 Surabaya. The approach used is descriptive qualitative with data collection techniques through participatory observation, in-depth interviews, documentation, and literature studies. The research instruments include observation guides, interview guides, assessment rubrics, field notes, and reflection sheets. Learning tools were developed using an ethnographic approach and the Problem Based Learning (PBL) learning model. The results of the study indicate that local wisdom-based learning in Semanggi Surabaya is able to increase students' active participation, strengthen understanding of the IPAS concept, and foster cultural awareness and character values. Students are able to produce poster works as a form of cultural preservation and show enthusiasm in the practice of making Semanggi. This learning also encourages teachers to be more creative in linking subject matter to the local context. The conclusion of this study states that the integration of local wisdom into contextual learning is effective in enriching students' learning experiences while preserving regional cultural heritage.